EDUCATION AND ETHICS: THE VALUE OF PRESENCE AND ALTERITY IN THE TEACHER'S TRAINING AND PRACTICE - Mantovani Leite, Sandra Regina; Trisltz, Rodolfo Gabriel; Carvalho, Alonso Bezerra de [UNESP] (Univ Estadual Paulista-unesp, Fac Ciencias Letras Assis, 2022)
This study aims to understand and deepen the reflection on the ethical dimension in teacher education and performance, emphasizing its importance for the development of a pedagogical praxis in favor of dialogical relationships. Faced with a pedagogical context marked by the conceptions present in contemporaneity that are guided by the condition that students are not seen as subjects of their own history and by the scientific development that privileges doing over thinking, we listed as main questions: what are the actions Could they help teachers to rethink their pedagogical practice, working so that human education becomes the essential aspect? Through a qualitative bibliographic research, based on authors such as Severino, A. J. (2011, 2010), Saviani (2015, 2016), Goergen (2011), Carvalho (2013, 2015, 2016), among others, we will seek to affirm the importance of alterity and presence in the relationship between teachers and students for a humanizing and emancipating education. We consider that every pedagogical action, from its origin and purposes, objectives and goals, has a close relationship with the Ethical Dimension and, therefore, they are ethical processes that, when carried out in the school institution, are committed to elevating the student from his condition as an individual in search of its humanization and emancipation.
Keywords: Education; Ethic; Teacher training; Humanization